The Role of Corporate Social Responsibility (CSR) in Mitigating Tax Evasion: A Comparative Study of Multinational Corporations (Issues in Social and Environmental Accounting (ISEA), 2026)
Corporate Social Responsibility (CSR) has become a central concept in the corporate sector, particularly for multinational corporations (MNCs). As global business operations have become more complex, scrutiny of corporate practices, especially regarding tax obligations, has                intensified. This study examines the role of CSR in mitigating tax evasion among MNCs,                focusing on how various CSR practices influence tax compliance behaviour. Although                      extensive research has addressed CSR's impact on corporate reputation, there is a notable gap in understanding how CSR specifically addresses tax evasion, particularly within diverse                regulatory environments. Employing a qualitative methodology that includes case studies,             interviews, and document analysis, this study provides comprehensive insights into the                     motivations and outcomes of CSR initiatives related to tax evasion. A comparative analysis of selected MNCs indicates that those with robust CSR frameworks tend to demonstrate lower instances of tax evasion, suggesting that CSR can deter unethical tax practices. These findings underscore the importance of transparency in CSR reporting, stakeholder engagement, and the integration of tax strategies within CSR frameworks. This study further highlights the                       significance of regulatory frameworks in enhancing CSR effectiveness and considers the                potential impact of technological advancements on the future of CSR and tax compliance. The implications for theory, policy, and practice are discussed, emphasising the necessity for MNCs to prioritise ethical tax behaviour as part of their CSR commitments. Future research directions include longitudinal studies, cross-industry and cross-regional comparative analyses, and                      investigations of emerging technologies to promote transparency and accountability in tax             practices.